Back pain in the under 20s would appear to be a 'red flag' of dubious significance: Results of a retrospective case note analysis. (April 2014) - Hiett, James; Chan, Daniel; Hourigan, Patrick
Abstract : Purpose: To assess whether being under the age of 20 is a significant 'red flag' in the presentation of first time low back pain. Method: Retrospective case note analysis of patients under 20 years of age, referred into a secondary care service with pain (not deformity) over a 1-year period. Results: The case notes of 86 new patients were reviewed. One patient with a serious pathology was identified, an eosinophilic granuloma. Fifty-six patients presented with non-specific mechanical spinal pain. Nine patients presented with a spondylolysis with or without associated spondylolisthesis and seven with disc degeneration/prolapse with nerve root pain. Thirteen patients (15%) received invasive treatment, six undergoing surgery (pars inter-articularis repair and discectomies), and seven had an injection (pars inter-articularis blocks, facet joint injections, transforaminal nerve root blocks or caudal epidural). Conclusion: This study does not support the hypothesis that being aged under 20 years at the time of presentation alone is a specific risk factor for serious pathology in patients with spinal pain.